Housekeeping in Tephritid insects: the best gene choice for expression analyses in the medfly and the olive fly - Sagri, Efthimia; Koskinioti, Panagiota; Gregoriou, Maria-Eleni; Tsoumani, Konstantina T.; Yiannis C. Bassiakos; Mathiopoulos, Kostas D. (Scientific Reports, 2017)
Real-time quantitative-PCR has been a priceless tool for gene expression analyses. The reaction, however, needs proper normalization with the use of housekeeping genes (HKGs), whose expression remains stable throughout the experimental conditions. Often, the combination of several genes is required for accurate normalization. Most importantly, there are no universal HKGs which can be used since their expression varies among different organisms, tissues or experimental conditions. In the present study, nine common HKGs (RPL19, tbp, ubx, GAPDH, α-TUB, β-TUB, 14-3-3zeta, RPE and actin3) are evaluated in thirteen different body parts, developmental stages and reproductive and olfactory tissues of two insects of agricultural importance, the medfly and the olive fly. Three software programs based on different algorithms were used (geNorm, NormFinder and BestKeeper) and gave different ranking of HKG stabilities. This confirms once again that the stability of common HKGs should not be taken for granted and demonstrates the caution that is needed in the choice of the appropriate HKGs. Finally, by estimating the average of a standard score of the stability values resulted by the three programs we were able to provide a useful consensus key for the choice of the best HKG combination in various tissues of the two insects.